A SEMICLASSICAL DESCRIPTION OF NONLOCAL EFFECTS ON BARRIER TRANSMISSION - Galetti, D.; Ribeiro, MAC (Royal Swedish Acad Sciences, 1992)
A quantum treatment for nonlocal factorizable potentials is presented in which the Weyl-Wiper quantum phase space description plays an essential role. The nonlocality is treated in an approximated form and allows for a Feynman propagator that can be handled in standard way. The semi-classical limit of the propagator is obtained which permits the calculation of the transmission factor in quantum tunnelling processes. An application in nuclear physics is also discussed.